Cardiac events and procedures following COVID-19 compared with other pneumonias: a national register study - Knut Stavem; Peder Langeland Myhre; Kristian Berge; Tarjei Øvrebotten; Birgitte Tholin (Open Heart)
Background Studies have shown an increased risk of cardiac disease following COVID-19, but how it compares to pneumonia of other etiologies is unclear.Aims To determine the incidence and HRs of cardiac disease in patients hospitalised with COVID-19 compared with other viral or bacterial pneumonias.Methods Using nationwide registry data, we estimated the incidence of cardiac events after hospitalisation with COVID-19 (n=2082) in February to November 2020 vs hospitalisation with viral (n=9018) or bacterial (n=29 339) pneumonia in 2018–2019. We defined outcomes using ICD-10 codes for incident myocarditis, acute myocardial infarction, atrial fibrillation/flutter, heart failure, ischaemic heart disease, other cardiac disease and total cardiac disease (any heart condition). We used Cox regression and logistic regression for analysis.Results Patients with COVID-19 had a mean (SD) age of 60 (18) years, compared with 69 (19) years for viral and 72 (17) years for bacterial pneumonia. Those with COVID-19 were more often male and had fewer comorbidities and fewer prior hospitalisations. Patients with COVID-19 had a lower hazard of new-onset cardiac disease compared with viral (HR 0.79 [95%CI 0.66 to 0.93]) and bacterial pneumonia (HR 0.66 [95%CI 0.57 to 0.78]), adjusted for age, sex, comorbidity, hospital admission prior year and respiratory support. Results were similar when including recurrent events.Conclusion Patients hospitalised with COVID-19 had a lower hazard of new-onset cardiac disease during the first 9 months after hospitalisation compared with patients with other viral or bacterial pneumonias after adjusting for multiple possible confounders. However, there may still be residual confounding from other or unknown factors.